The sixth and seventh cholera pandemics are due to independent clones separately derived from environmental, nontoxigenic, non-O1 Vibrio cholerae. - Karaolis, D K (1995)
The DNA sequences of the asd genes from 45 isolates of Vibrio cholerae (19 clinical O1 isolates, 2 environmental nontoxigenic O1 isolates, and 24 isolates with different non-O1 antigens) were determined. No differences were found within either sixth- or seventh-pandemic isolates; however, variation was found between the two forms and among the non-O1 isolates. O139 isolates had sequences identical to those of seventh-pandemic isolates. Phylogenetic trees with Vibrio mimicus as the outgroup suggest that the sixth-pandemic, seventh-pandemic, and U.S. Gulf isolates are three clones that have evolved independently from different lineages of environmental, nontoxigenic, non-O1 V. cholerae isolates. There is evidence for horizontal transfer of O antigen, since isolates with nearly identical asd sequences had different O antigens, and isolates with the O1 antigen did not cluster together but were found in different lineages. We also found evidence for recombination events within the asd gene of V. cholerae. V. cholerae may have a higher level of genetic exchange and a lower level of clonality than species such as Salmonella enterica and Escherichia coli.